Experimental Study on the Distribution Trends of Fouling on a Compressor Blade - Jie Tang; Dianrong Gao; Liwen Wang; Jinjian Huo (International Journal of Photoenergy)
The formation of a scale on a compressor blade surface is inevitable, and the study of the distribution of the scale can provide effective guidance for the cleaning of a wing engine. Using the waste liquid collected from the engine during the wing water washing process as a data sample, the main components of compressor blade surface fouling were analysed, which included 49.9% SiO2, 14.5% FeO, 11.5% Al2O3, 9.4% CaO, etc. Based on JKR contact theory, a model for calculating the total thickness of the fouling layer on the blade surface was established. Through a simulation experiment on the fouling of a blade surface, the number of particulates deposited on the pressure surface was lower than the amount of the secondary deposition mass on the suction surface. From contrastive analysis of the results of perforation, the fouling is divided into three types: loose, dense, and transitional. The surface of a single blade can be divided into four different fouling areas. The parameters of the engine cleaning process can be designed according to the characteristics of the fourth area.